If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + x = 4x + 23 + -6x Reorder the terms: -13 + x = 23 + 4x + -6x Combine like terms: 4x + -6x = -2x -13 + x = 23 + -2x Solving -13 + x = 23 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -13 + x + 2x = 23 + -2x + 2x Combine like terms: x + 2x = 3x -13 + 3x = 23 + -2x + 2x Combine like terms: -2x + 2x = 0 -13 + 3x = 23 + 0 -13 + 3x = 23 Add '13' to each side of the equation. -13 + 13 + 3x = 23 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = 23 + 13 3x = 23 + 13 Combine like terms: 23 + 13 = 36 3x = 36 Divide each side by '3'. x = 12 Simplifying x = 12
| .29(14q+2.5)-3q=9 | | -1.5b+7a+5b= | | 3(x-7)=2x | | 3b+2a= | | -10x-19=-19-8x | | -x+9=1-2x | | 1=-x+1 | | 7n^3+125n=0 | | 4a+4+2a+36= | | 10x+2x=144 | | 146=47+x | | 8x=6.5 | | 2x-10=-10-3x | | .5(108+f)=73 | | 8n-4=28 | | 29+x=13 | | x-12=114+3x | | -2x^2+16=-7x | | 6+2w=w-6 | | -2x-80=-x^2 | | x+(-1)=221+2x | | 15x-15x-30=0 | | 2a+9=7 | | -6x-18=6 | | 9n+10=-17 | | 15+2n=8+3n | | 12=-x+1 | | -7x-15=34 | | (.25)16+30=x | | x^2-9=9 | | 5*5-6=x | | K+3K+32=27+2+5K |